2023
DOI: 10.1039/d3mh00775h
|View full text |Cite
|
Sign up to set email alerts
|

High-performance asymmetric electrode structured light-stimulated synaptic transistor for artificial neural networks

Yixin Ran,
Wanlong Lu,
Xin Wang
et al.

Abstract: Photonics neuromorphic computing shows great prospect due to the advantages of low latency, low power consumption and high bandwidth. Transistors with asymmetric electrode structures are receiving increasing attention due to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 83 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…1(f) and Table S1 (ESI†). The E for each photosynaptic event is calculated by the following formula: 46 Δ E = V × I × Δ t where V is the voltage applied to both ends of the device; I represents the peak value of the EPSC after one light pulse, and Δ t is the optical pulse width. The power consumption and S of the device prepared in this study are among the best parameters for the reported optoelectronic synapse.…”
Section: Resultsmentioning
confidence: 99%
“…1(f) and Table S1 (ESI†). The E for each photosynaptic event is calculated by the following formula: 46 Δ E = V × I × Δ t where V is the voltage applied to both ends of the device; I represents the peak value of the EPSC after one light pulse, and Δ t is the optical pulse width. The power consumption and S of the device prepared in this study are among the best parameters for the reported optoelectronic synapse.…”
Section: Resultsmentioning
confidence: 99%